2017
DOI: 10.1007/jhep01(2017)034
|View full text |Cite
|
Sign up to set email alerts
|

Multiloop amplitudes of light-cone gauge NSR string field theory in noncritical dimensions

Abstract: Feynman amplitudes of light-cone gauge superstring field theory are ill-defined because of various divergences. In a previous paper, one of the authors showed that taking the worldsheet theory to be the one in a linear dilaton background Φ = −iQX 1 with Feynman iε (ε > 0) and Q 2 > 10 yields finite amplitudes. In this paper, we apply this worldsheet theory to dimensional regularization of the light-cone gauge NSR superstring field theory. We concentrate on the amplitudes for even spin structure with external l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 58 publications
(175 reference statements)
0
19
0
Order By: Relevance
“…Although Lorentz invariance is broken by doing so, it does not cause so much trouble because the light-cone gauge theory is a completely gauge-fixed theory. In [13], we have shown that the multiloop amplitudes corresponding to the Riemann surfaces with even spin structure involving external lines in the (NS,NS) sector can be calculated using the dimensional regularization and the results coincide with those of the first-quantized approach.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…Although Lorentz invariance is broken by doing so, it does not cause so much trouble because the light-cone gauge theory is a completely gauge-fixed theory. In [13], we have shown that the multiloop amplitudes corresponding to the Riemann surfaces with even spin structure involving external lines in the (NS,NS) sector can be calculated using the dimensional regularization and the results coincide with those of the first-quantized approach.…”
Section: Introductionmentioning
confidence: 58%
“…B and F denote the sums over bosonic and fermionic string fields respectively. The three-string vertices V 3 | are elements of H * ⊗ H * ⊗ H * whose definition can be found in [13,15,16]. Here H * denotes the dual space of H.…”
Section: Light-cone Gauge Superstring Field Theorymentioning
confidence: 99%
See 3 more Smart Citations